IMPLEMENTASI FUNGSI BHABINKAMTIBMAS DALAM PENYELESAIAN MASALAH - Jonathan Harianja; Fahmi; M. Fadly Daeng Yusuf (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
This study aims to examine the implementation of the Bhabinkamtibmas function in problem solving within the jurisdiction of the Meranti Islands Police Resort (Polres Kepulauan Meranti), the obstacles encountered, and the efforts made to overcome those obstacles. Bhabinkamtibmas plays a significant role as the frontline of the Indonesian National Police in maintaining public security and order through partnership approaches, community development, and the preventive and restorative resolution of social problems within society. This research employs a sociological legal research method with an empirical approach. Data were collected through interviews, observations, and literature studies. The research was conducted at the Meranti Islands Police Resort. Data were analyzed qualitatively and conclusions were drawn deductively. The results indicate that the implementation of the Bhabinkamtibmas function in problem solving at Polres Kepulauan Meranti has been carried out through mediation, deliberation, and facilitation of the settlement of social conflicts and minor criminal cases occurring in the community. The implementation of this function has contributed to maintaining public security and order while reducing the potential for conflicts to proceed to formal judicial processes. Nevertheless, several obstacles remain, including the limited number of Bhabinkamtibmas personnel compared to the size of their assigned areas, the low level of public understanding regarding problem-solving mechanisms, and inadequate supporting facilities and infrastructure. Efforts to address these challenges include increasing public awareness and socialization programs, strengthening coordination with village governments and community leaders, and enhancing personnel capacity through education and training.